Aplikasi Seven Tools untuk Mengurangi Cacat Produk White Body pada Mesin Roller - Tio Prima Matondang; Muhammad Mujiya Ulkhaq (Universitas Serang Raya, 2018)
This study aims to demonstrate effectively application of the seven tools as one of the quality management tools to reduce product defects. A case study has been conducted in the production of white body at PT. XYZ, which is located in Semarang. The high percentage of defects is considered as one causes of not attaining the target of the company. Seven tools, which consist of check sheet, stratification, histogram, scatter diagram, control chart, Pareto chart, and cause-and-effect diagram, are used to analyze the causes of the defects. Based on data processing results, there are eight types of defects, namely: tobi, hage, burn back, crolling, saya boro, broken back stamp, hama kake, and nama kire. Recommendations for improvement have been proposed using 5W+1H analysis to improve the company's quality control performance and minimize product defects.